Reengineering Filipino, English, and the lingua Franca in basic education - Cruz, Isagani R. (Philippine Journal of Linguistics, 2003)
The 2002 Basic Education Curriculum (BEC) involves a reduction of several subjects or learning areas to five: Filipino, English, Mathematics, Science, and Makabayan. The learning competencies previously assigned to the discarded subjects have been redistributed to these five, particularly to Filipino, English and Makabayan. At the same time, the Lingua Franca Project, which experiments on the use of regional vernaculars in selected schools, has been continued and even expanded to include the use of local vernaculars. How are language learning elements integrated into the new BEC? What lessons have been learned so far about language planning, curriculum planning, teacher training, and change management?